الصراع الدوناتي الكاثوليكي في المغرب القديم - عولمي, الربيع (جامعة الوادي - University of Eloued, 2017)
تهدف هذه الدراسة إلى إبراز جذور الانشقاق الدوناتي وخلفيات الصراع الدوناتي-الكاثوليكي في المغرب القديم الذي يعود إلى اضطهادات الامبراطور "ديوكليتيانوس" للمسيحيين خلال الفترة (303م-305م) والتي أدت إلى ارتداد عدد كبير منهم، وطرحت مشكلة الانقسام بقوة في الكنيسة الإفريقية. وتكرس الانشقاق على إثر سيامة "كايكليانوس" أسقف قرطاجة في 311م، بعد وفاة "مونسوريوس"، ووجدت الكنيسة الإفريقية نفسها منقسمة بين أسقفين وحزبين: الكنيسة الدوناتية والكنيسة الكاثوليكية. دخل القديس "أوغسطين" حلبة الصراع على الصعيد اللاهوتي منذ 392م على رأس أسقفية هيبو-ريجيوس (عنابة حاليا)، وترأس مجمع هيبون سنة 393م الذي أدان الدوناتيون. وعلى مدى أكثر من قرن من الزمن وقفت الدوناتية في وجه الكنيسة الكاثوليكية، والسلطة الزمنية الرومانية التي تدعمها حتى انعقدت مناظرة قرطاجة بطلب من الإمبراطور التي أقرت مبدأ حظر وتحريم الدوناتية رسميا سنة 411م. This study aims at highting the roots of the Donatical schism, and the background of the Donatical-Catholic conflict in the ancient maghreb, which dates back to the persecution of christians by the emperor Dioclétianus during the period (303- 305 A.D.), which led to the rebelling of many of them. The problem of devision nas strongly raised in the African church. The schism is dedicated to the influence of Caecilianus Bishop of Carthage in 311 A.D., after death of Mensurius, the African church found itself was divided between two Bishops and two parties : the Donatist church and the Catholic church. Saint -Augustine entered the arena of conflict since 392 A.D., at the head of his Bishop Hippo-Régius (Annaba currently), he presided over the Hippone complex in 393 A.D., which condemned the Donatists, and for more than a century, The Donatist Church stood in the face the Catholic church and the Roman temporel authority that supported it until the Carthage debate was help at the request of the emperor, who approved the principle of attending and forbidding the Donatism officially in 411 A.D.
مقال
Keywords: الانشقاق، الكنيسة الدوناتية، الكنيسة الكاثوليكية، القديس "أوغسطين"، مناظرة قرطاجة; Saint Augustine, the Donatist church, the Catholic church, the Carthage debate, the Schism